2018
DOI: 10.1186/s12931-017-0712-9
|View full text |Cite
|
Sign up to set email alerts
|

The association of the N-terminal pro-brain-type natriuretic peptide response to exercise with disease severity in therapy-naive pulmonary arterial hypertension: a cohort study

Abstract: BackgroundWhile the N-terminal pro-brain-type natriuretic peptide (NT-proBNP) at rest is known to be associated with prognosis in pulmonary arterial hypertension (PAH), it is unclear if the NT-proBNP response to exercise (ΔNT-proBNP) can contribute to a better assessment of disease severity.MethodsWe investigated the association of NT-proBNP values at rest and during peak exercise with hemodynamics and cardiopulmonary exercise testing parameters in 63 therapy-naive PAH patients.ResultsThe median NT-proBNP incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Decreases in NT-proBNP with endurance exercise, but increases with strength exercise, have been described in sedentary individuals [58]. However, KUTSCH et al [59] in a study of 63 patients, concluded that accounting for exercise-related changes in NT-proBNP did not improve correlation with other surrogate markers of disease.…”
Section: Bnp and Nt-probnp Considerations For Samplingmentioning
confidence: 99%
“…Decreases in NT-proBNP with endurance exercise, but increases with strength exercise, have been described in sedentary individuals [58]. However, KUTSCH et al [59] in a study of 63 patients, concluded that accounting for exercise-related changes in NT-proBNP did not improve correlation with other surrogate markers of disease.…”
Section: Bnp and Nt-probnp Considerations For Samplingmentioning
confidence: 99%
“…Brain natriuretic peptide (BNP) is an established and widely used clinical parameter for heart function and failure, and ventricular remodelling. While BNP was shown being a prognostic marker in PAH [27], others ruled out the NT-proBNP response to exercise as a disease severity assessment marker of PAH [28]. No significant upregulation of BNP was detectable in the RV due to the application of different diets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NT-proBNP levels have also been associated with clinical outcomes in patients with pre-capillary and post-capillary pulmonary hypertension. 19,20 In response to a pressure or volume overload, NT-proBNP levels are an immediate reflection of RV Figure 3 Incremental prognostic value of right ventricular NT-proBNP dichotomized by 1500 pg/mL in predicting hospitalization for heart failure in patients with Group I PAH. NT-proBNP, N-terminal pro B-type natriuretic peptide; ROC, receiver operating characteristic curve; RV, right ventricular.…”
Section: Discussionmentioning
confidence: 99%
“…NT‐proBNP, a cleavage product of BNP, is secreted from membrane granules of ventricular cardiomyocytes and is an established biomarker for the diagnosis of HF. NT‐proBNP levels have also been associated with clinical outcomes in patients with pre‐capillary and post‐capillary pulmonary hypertension 19,20 . In response to a pressure or volume overload, NT‐proBNP levels are an immediate reflection of RV dilatation and deterioration of systolic function 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation